2003
DOI: 10.1074/jbc.m303455200
|View full text |Cite
|
Sign up to set email alerts
|

Covalent and Non-covalent Interactions of βig-h3 with Collagen VI

Abstract: Transforming growth factor-␤ induced gene-h3 (␤ig-h3) was found to co-purify with collagen VI microfibrils, extracted from developing fetal ligament, after equilibrium density gradient centrifugation under both nondenaturing and denaturing conditions. Analysis of the collagen VI fraction from the non-denaturing gradient by gel electrophoresis under non-reducing conditions revealed the present of a single high molecular weight band that immunostained for both collagen VI and ␤ig-h3. When the fraction was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…The binding site is located close to the amino-terminal end of the collagen VI molecule. Additional binding assays have demonstrated that ␤ig-h3 binds in vitro to collagen VI, but in a non-covalent manner (32). The ␤ig-h3 attachment site on collagen VI appears to be close to those documented for the small leucinerich proteoglycans (SLRP), decorin and biglycan, and matrilins (33)(34)(35).…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…The binding site is located close to the amino-terminal end of the collagen VI molecule. Additional binding assays have demonstrated that ␤ig-h3 binds in vitro to collagen VI, but in a non-covalent manner (32). The ␤ig-h3 attachment site on collagen VI appears to be close to those documented for the small leucinerich proteoglycans (SLRP), decorin and biglycan, and matrilins (33)(34)(35).…”
mentioning
confidence: 58%
“…Human r␤ig-h3 and pepsin-treated collagen VI were prepared and purified as described previously (32,37). Purified r␤ig-h3 was stored at 4°C in 50 mM Tris buffer, pH 7.4, containing 500 mM NaCl to prevent self-aggregation prior to aggregation experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of TGFBI on adhesion are mediated through interactions with various integrins including α1β1, α3β1, αvβ3 and αvβ5 (LeBaron et al 1995, Ohno et al 1999, Bae et al 2002, Jeong & Kim 2004, Kim & Kim 2008) via the different integrin-binding motifs. TGFBI also functions as a linker protein and connects many matrix proteins including collagens (type I, II and IV), fibronectin (Billings et al 2002) and proteoglycans (biglycan and decorin) with each other (Gibson et al 1997, Billings et al 2002, Hanssen et al 2003, Reinboth et al 2006.…”
Section: Role Of Tgfbi In Ovarian Cancermentioning
confidence: 99%